Fetal risk factors associated to preterm delivery case control study - Salvador, Jorge (2015)
OBJECTIVES: To determine the factors of maternal and fetal risks that are associated with premature birth. Material and Methods: A retrospective, comparative, case-control, based on medical records and interviews of patients whose births were attended at the Cayetano Heredia National Hospital between January 1 and March 31, 2003. Study was included all cases (106 premature) and controls (term 1325) that occurred in the study period. In the statistical evaluation the multivariate analysis (logistic regression) was used; thus the odds ratio (ratio of products) and the confidence interval for each variable was determined. The significance level used was 95% (p <0.05]. RESULTS: maternal risk factors were age <20 years, history of prematurity, inadequate prenatal care, urinary tract infection, premature rupture of membranes, and preeclampsia-eclampsia antepartum haemorrhage and fetal risk factors, stillbirth, twins and poor presentation.